Collective collapse in football - Apitzsch, E. (Football Psychology - From Theory to Practice, 2019)
Collective collapse occurs when a majority of the players in a team suddenly perform below expected level in a match, in spite of a satisfactory start, or when a team underperforms right from the start. Research results from a study on 146 male players and 15 coaches in various team sports at the elite level, and a study on a team involved in a collective collapse, and the opposite, a winning turnaround. The behaviour of the players and the coaches accounted for 69.6% of the reasons given for the occurrence of a collective collapse. Lack of communication and lack of role acceptance were given as the main factors. A collective collapse is usually followed by negative emotions, which spread among the team resulting in emotional contagion. In order to avoid a collective collapse or take appropriate action in case it occurs, it is suggested that players focus on the right goal (process goals), use constructive communication (between coach-players, and between players), and execute the expected role performance in their position. In addition, it is suggested that teams appoint 2-3 emotional leaders among the starting players, who are regarded as being expressive, interactive, and contributing to team performance as well as social cohesion. The role of the emotional leader is to implement a positive team atmosphere in times of adversity.